Structural Characterizations of Palladium Clusters Prepared by Polyol Reduction of [PdCl4]2− Ions. (17th March 2016) - Schiavo, Loredana; Aversa, Lucrezia; Tatti, Roberta; Verucchi, Roberto; Carotenuto, Gianfranco
Abstract : Palladium nanoparticles are of great interest in many industrial fields, ranging from catalysis and hydrogen technology to microelectronics, thanks to their unique physical and chemical properties. In this work, palladium clusters have been prepared by reduction of [PdCl4 ] 2− ions with ethylene glycol, in the presence of poly(N-vinyl-2-pyrrolidone) (PVP) as stabilizer. The stabilizer performs the important role of nucleating agent for the Pd atoms with a fast phase separation, since palladium atoms coordinated to the polymer side-groups are forced at short distances during nucleation. Quasispherical palladium clusters with a diameter of ca. 2.6 nm were obtained by reaction in air at 90°C for 2 hours. An extensive materials characterization by transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and other characterizations (TGA, SEM, EDS-SEM, and UV-Vis) has been performed in order to evaluate the structure and oxidation state of nanopalladium.